Towards a European key performance indicator for safe urban roads: lessons from the Trendline project - Wendy Weijermars; Elisabete Rodrigues; Johannes Mesimäki; Simon Sternlund; Maria Georgieva; Jan Hendrik van Petegem; Teun Uijtdewilligen; Augusto Torbay; Ana Amaro; Ana Vidigal; Fernando Rosa; Wouter Van den Berghe (Traffic Safety Research)
Key Performance Indicators (KPIs) are an important instrument for road safety policy making. This paper presents a KPI for safe urban roads that was developed and tested in the European Trendline project. Based on discussions with 18 experts from 8 countries, it was decided to start with the basic indicator ‘Share of 30 km/h road length of the total length of urban roads’ which was tested in five pilot countries using available local, national and international (GIS) databases. The share of 30 km/h roads appeared to differ considerably between the pilot countries, ranging from less than 1% in the city of Silistra in Bulgaria to 73% in the Netherlands. The pilots showed that it is possible to calculate the KPI, although it is important to check the quality of the speed limit data and there will be some differences in selections due to data availability and local context. Also the use of additional indicators related to the concept of safe speeds was explored in the pilots. The calculation of these indicators appeared to be more challenging and further research is recommended to further develop these additional KPIs.